MODELLING OF MATHEMATICAL PROCESSES AS A SCIENTIFIC COGNITION IN HIGH SCHOOL - Reihenova, Austra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The topicality of the article relates to the use of modelling in a real, complicated and complex process, with the need to forecast the progress and results of the occurrence. Article problem: In school, the focus is on building theoretical models, without real-life context. In real life, the problems are interdisciplinary, more difficult to define than in the theoretical model. The student should be able to transfer knowledge and concepts from one learning discipline in which he can deal with the problem to another. Mathematical modelling offers opportunities to connect and use knowledge from different disciplines. The aim of the article is to stimulate interest in the use of diverse learning approaches and forms, on the learning of mathematics as science, on its application in other scientific disciplines to address problems, on mathematics as a form of systemic thinking and on mathematical modelling as a learning method. The study used student test papers and open-ended questionnaires to collect data. The research used data triangulation method for data processing.